Study of degradation mechanism of metal nanocrystal-based gate stacks - Chen, Yining (2012)
This thesis focuses on the degradation and reliability mechanism of the metal nanocrystal-based Al2O3/SiO2 gate stacks which is believed to be a promising candidate for next generation nonvolatile memory. A series of novel approaches were used to obtain in-depth knowledge of the gate stack in terms of charge retention, gate dielectric breakdown and post-breakdown recovery. We also discuss the phenomenon of the post-breakdown recovery on the metal nanocrystal-based gate stack and the possibility of such charge-trapping gate stack as a candidate for a resistive switching memory cell.